2020
DOI: 10.3390/microorganisms9010082
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Adult Fasciola spp. Using Matrix-Assisted Laser/Desorption Ionization Time-of-Flight (MALDI-TOF) Mass Spectrometry

Abstract: Fascioliasis is a neglected trematode infection caused by Fasciola gigantica and Fasciola hepatica. Routine diagnosis of fascioliasis relies on macroscopic identification of adult worms in liver tissue of slaughtered animals, and microscopic detection of eggs in fecal samples of animals and humans. However, the diagnostic accuracy of morphological techniques and stool microscopy is low. Molecular diagnostics (e.g., polymerase chain reaction (PCR)) are more reliable, but these techniques are not routinely avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…For the identification of Fasciola spp. [17], cyathostomins [27], and lice [26], 70% (v/v) ethanol was used as a storage solution, while studies on Anisakis spp. [19], Dirofilaria spp., and Ascaris spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the identification of Fasciola spp. [17], cyathostomins [27], and lice [26], 70% (v/v) ethanol was used as a storage solution, while studies on Anisakis spp. [19], Dirofilaria spp., and Ascaris spp.…”
Section: Discussionmentioning
confidence: 99%
“…Each part was then transferred to a new tube for subsequent MALDI-TOF MS measurements. For protein extraction, we employed a previously developed protocol [17].…”
Section: Differential Sample Storage Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fascioliasis is a parasitic disease which is of concern to veterinary and public health sector worldwide (Sy et al 2021). The genetic markers ITS 1 and ITS 2 genes of ribosomal DNA have been utilized to discriminate between Fasciola hepatica and Fasciola gigantica (Amor et al 2011;Dar et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the MALDI-TOF technique is that once a robust, generalized protein extraction protocol and a database incorporating a variety of protein spectra from different microorganisms have been established, there is no need to perform a multitude of different assays to identify the pathogen, resulting in fast and cost-effective identification [ 25 ]. In routine diagnostics, MALDI-TOF MS has become a standard tool for identification of bacteria and yeast [ 25 , 26 , 27 ] and has also been applied in parasitology research [ 28 , 29 , 30 , 31 ]. However, in the field of foodborne parasitology, only two studies have demonstrated the use of this technique in the framework of official meat inspection for Trichinella spp.…”
Section: Introductionmentioning
confidence: 99%